Implementation of rational emotive behavior therapy (REBT) in handling negative student behavior - Nur Khairun Hanifah; Ifdil Ifdil; Sharifah Nurulhuda Tuan Mohd Yasin (RedWhite Press, 2024)
Negative behavior among secondary school students is a problem that is still frequently found in educational environments and has a significant impact on the learning process as well as students’ social-emotional development. These behaviors include rule violations, lack of discipline, low academic responsibility, and aggressive actions toward peers and teachers. This problem is influenced not only by environmental factors but also by internal factors, particularly students’ irrational thinking patterns in interpreting events. This article aims to examine in depth the application of Rational Emotive Behavior Therapy (REBT) in addressing negative behavior among secondary school students. The method used is a literature study by reviewing various relevant books and scientific journals. The results of the study show that negative behavior is often rooted in students’ irrational beliefs about certain events. Through the disputing technique in REBT, students are helped to challenge these beliefs and replace them with more rational, logical, and realistic thinking patterns. This change in thinking patterns leads to more adaptive and constructive behavioral changes in daily life. Thus, REBT can be an effective approach in school guidance and counseling services.